ADJUSTMENT OF INTERNATIONAL MODELS PERTAINING TO THE FUNCTIONING OF MECHANISMS OF DEVELOPMENT OF PROFESSIONAL POTENTIAL OF CIVIL SERVANTS IN UKRAINE - Polishchuk I.V. (Pressing Problems of Public Administration, 2017)
The analysis of distinguishing characteristics and peculiar features of international models pertainingto the functioning of mechanisms of development of professional potential of civil servants hasbeen carried out. Based on the best practices the fundamental mechanisms for the insurance ofdevelopment of professional potential of civil servants within the system of public administration havebeen outlined. The article designates the key tendencies in the adjustment of international modelspertaining to the functioning of mechanisms of development of professional potential of civil servantsto the national system of public administration.